Power-Dependence Relations for Policy Formulation Gender Responsive Budgeting Case in West Sumatera Indonesia - Rozidateno Putri Hanida; Roy Valiant Salomo; Achmad Lutfi (Greenation Research & Yayasan Global Resarch National, 2026)
While gender-responsive budgeting (GRB) aims to empower women, its execution often overlooks complex cultural landscapes. Addressing a critical research gap, this study moves beyond standard structural GRB assessments by examining its implementation within West Sumatra’s matrilineal society a unique context where women hold customary legitimacy but lack formal political influence. The novelty of this research lies in integrating policy network analysis with indigenous cultural paradigms to expose the exact disjuncture between symbolic gender authority and actual bureaucratic power. Through document analysis, interviews, and participatory observation, the study maps regional planning actors, revealing a narrow, hierarchical network. Power remains heavily concentrated among male bureaucrats and local parliaments, while women's organizations and civil society languish at the margins. This empirically confirms the